Towards a spatial critique of ideology: architecture as a test - Kurnicki, Karol (Journal of Architecture and Urbanism, 2014)
The article presents the outline for the theory of ideological space. The ideological properties of space are reconsidered by the juxtaposition of Lefebvre’s and Bourdieu’s theories. The resultant reconciliation points towards the notion of spatial critique of ideology as well as the possibility of employing ideology for critique of space. The notion of a test (as characterized by Boltanski) is introduced to show the importance of capabilities of actors and objects in the process of critique. The article emphasizes the exceptional significance of architecture for the construction of critical positions. The architecture is described as a form of a test. In so doing, the architecture is characterized as one of the essential elements of possible social emancipation. In effect, both the social responsibilities of the architecture and its critical role are underscored.